The influence of content marketing on customer brand engagement towards online herbal cosmetic store in Thailand - Bunpis, Laila; Haron, Mahmod Sabri (2014)
The growing of health and beauty industries plays important roles in national economic development. Thailand is one of the largest herbal markets. Many Thai entrepreneurs pay attention to produce Thai herbal cosmetic to serve online marketing. This channel has selected from small and medium enterprises to access their target groups.Among fierce competitions,Customer Brand Engagement is an essential strategy which SMEs should highlight due to it can help increasing the amount of customer online purchasing.Content Marketing is one of techniques to build customer brand engagement, but still lack of empirical investigation.Hence, to narrow this gap, this paper aims to study background of knowledge about the influence of the content marketing on customer brand engagement towards online herbal cosmetic store in Thailand. This study focused on analyzing documentary research and review literature. The result of this paper will provide foundational insights and extend knowledge about customer brand engagement and content marketing which may be used to guide future study.In addition, it leads to the enhanced willingness of customers that in turn increase online purchasing and revenues of SMEs firms.